Direct calculation design method for atrium in superstructure of large cruise ship - Xiangshao KONG; Gan SHI; Zhuo WANG; Yue ZHU; Weiguo WU (Zhongguo Jianchuan Yanjiu, 2023)
ObjectivesThe atrium structure is an important functional cabin in the superstructure of a large cruise ship. Atriums have a large spatial span and are always subjected to complex loads. A fast and reliable safety assessment simulation method for atrium structures is required to assist in their structural design.MethodsBased on the Guidance for Direct Calculation of Local Structures of Cruise Ships 2021 by the China Classification Society (CCS) and the loading characteristics of atriums, a direct calculation design method is proposed in which loads on structures are equivalent to combined simplified loads in three groups, namely longitudinal bending, vertical shear and local cargo pressure.ResultsThe results of the proposed direct calculation design method of a specific atrium structure are in good agreement with the whole-ship finite element analytical results, verifying its effectiveness.ConclusionsThis study can provide guidance for the design process of atrium structures in large cruise ships.